An analysis and projection of diabetes prevalence in East England region - Xie, Ying; Anjum, Nasreen; Pierscionek, Barbara; Kiran, Mahreen; Partac, Magdalena; Wang, Yue (Springer, 2026)
Background: Diabetes prevalence continues to rise in England, placing increasing pressure on primary and specialist healthcare services. This study examined how demographic, socioeconomic, and healthcare access factors influence Diabetes Mellitus register size across six Integrated Care Systems (ICSs) in the East of England and generated scenario based projections of future diabetes burden and specialist workforce requirements. Methods: A longitudinal panel design was applied using annual data (2012–2021) for six ICSs. Descriptive trend analysis summarised changes in diabetes registers, GP practice numbers, GP list size, deprivation (IMD scores), and population density. The association between these factors and Diabetes Mellitus register size was quantified using a fixed effects panel regression model, selected through F-tests, Breusch–Pagan LM tests, and Hausman specification testing. Future diabetes registers (2023–2027) were estimated using a regression based deterministic projection framework integrating: (i) model based forecasting, (ii) four scenario models based on plausible changes in population growth, deprivation, and GP capacity, and (iii) linear trend extrapolation of endocrinology consultant workforce numbers. Results: Diabetes registers increased across all ICSs, with the region experiencing a 13% rise between 2012 and 2021. Regression findings showed that higher deprivation strongly predicted larger diabetes registers (β=2824.24, p<0.001), while increases in GP list size and GP practice numbers were also significant predictors. Under Scenario I, projected diabetes registers for 2023 ranged from 60,603 (Cambridgeshire and Peterborough) to 85,574 (Hertfordshire and West Essex). Scenario II, which incorporated greater increases in deprivation, produced larger projected registers across all ICSs, including 75,463 in Bedfordshire and 88,399 in Hertfordshire. Patient to consultant ratios were projected to increase in Bedfordshire and Mid and South Essex, suggesting potential specialist workforce shortages. Conclusion: Demographic growth, rising deprivation, and pressures in primary care are key drivers of the increasing diabetes burden in the East of England. Projection results indicate that several ICSs may face widening gaps between patient demand and specialist capacity. Strengthening consultant staffing, directing resources toward more deprived areas, and supporting primary care resilience will be essential to maintain equitable diabetes care in future years.
Keywords: 42 Health Sciences; Diabetes; 8.1 Organisation and delivery of services; Public Health; 4202 Epidemiology; 4203 Health services and systems; 4206 Public health